Transcriptomic Changes of Bemisia tabaci Asia II 1 Induced by Chilli Leaf Curl Virus Trigger Infection and Circulation in Its Vector - Nekkanti, Aarthi; Chakraborty, Prosenjit; Ghosh, Amalendu; Iquebal, Mir Asif; Jaiswal, Sarika; Baranwal, Virendra Kumar (Frontiers in Microbiology, 2022)
Bemisia tabaci (Hemiptera: Aleyrodidae) is a highly efficient vector in the spread of chilli leaf curl virus (ChiLCV, Begomovirus) which is a major constraint in the production of chilli in South Asia. Transcriptome analysis of B. tabaci post-6 hrs acquisition of ChiLCV showed differential expression of 80 (29 upregulated and 51 downregulated) genes. The maximum number of DEGs are categorized under the biological processes category followed by cellular components and molecular functions. KEGG analysis of DEGs showed that the genes are involved in the functions like metabolism, signaling pathways, cellular processes, and organismal systems. The expression of highly expressed 20 genes post-ChiLCV acquisition was validated in RT-qPCR. DEGs such as cytosolic carboxypeptidase 3, dual-specificity protein phosphatase 10, 15, dynein axonemal heavy chain 17, fasciclin 2, inhibin beta chain, replication factor A protein 1, and Tob1 were found enriched and favored the virus infection and circulation in B. tabaci. The present study provides an improved understanding of the networks of molecular interactions between ChiLCV and B. tabaci. The candidate genes involved in ChiLCV transmission would be novel targets for the management of the B. tabaci-begomovirus complex.